The Rights of A Working Wife to Maintenance: An Islamic Perspective - Hamidu Ardo; Abubakar Ibrahim Adamu (MAQOLAT: Journal of Islamic Studies, 2025)
Sharia imposes a duty on the husband to maintain his wife arises when the marriage contract was completed. The right of the husband to maintain his wife continuous until the contract of the marriage comes to an end through divorce or death of the husband. In Islam it is the duty of the husband to provide for his family expenses. In this respect the wife may have wealth more than the husband but still she has no obligation to contribute to the maintenance of the family. The paper is to examine the provisions of sharia on the husband to maintain a wife generally and also the maintenance of a working wife. The paper will analyses the law on the extended duty of the husband to maintain the wife even though the wife is working and earning a good salary.